STUDY ON THE USE OF ANTIEMETIC DRUGS IN BREAST CANCER PATIENTS UNDERGOING CHEMOTHERAPY - Vincensia Vonny Fredianto Putri (Indonesian Pharmacopeia Journal, 2024)
Breast cancer is a malignant disease that most commonly attacks women. Therapies used in the treatment of breast cancer are divided into local and systemic therapies. Local therapy, namely surgical therapy and radiotherapy, for systemic therapy, namely hormone therapy, chemotherapy. Chemotherapy is a treatment option for breast cancer that has metastasized or is at an advanced stage. The most common side effect of chemotherapy is nausea, vomiting, so to prevent nausea and vomiting due to chemotherapy, do antiemetic therapy before and after chemotherapy. The design of this research is non-experimental research, namely descriptive quantitative, the population in this study was 150 and the sample in this study was 39 patients. From the results of data analysis, it was found that the most widely used class of premedication drugs before chemotherapy was a combination of ondansetron injection 4 mg, ranitidine injection 100 mg and dexamethasone injection 15 mg. Meanwhile, the use of post-medication medication after chemotherapy uses a single therapy of 8mg ondansetron injection, and for oral medication taken home by the patient uses a single therapy of 4mg ondansetron, The use of antiemetic drugs to treat nausea and vomiting is given pre-chemotherapy and post-chemotherapy drugs.